Fairness, outcomes, expectations : exploring drivers of individual reactions to planned organisational change - Fortin, Marion (Trinity College (Dublin, Ireland). Trinity Business School, 2006)
The principal objective of this study is to investigate the link between employees' experience of and reactions to organisational change through the frame work of organisational justice . This study differentiates between four dimensions of organisational justice , namely distributive, procedural, interpersonal and informational justice, and takes into account both anticipated and perceived fairness. Drawing on a review of extant contributions addressing organisational justice in change contexts, I formulated a chronological research model. Within this research model, a number of questions and hypotheses to guide my empirical investigation have been developed. The hypotheses concern the relationships between anticipated and perceived fairness of change along the four dimensions of organisational justice and the intentions to resist the change or support the change, at different phases of planned change (discovery and aftermath stages).
Keywords: Business Studies, Ph.D.; Ph.D. Trinity College Dublin